Improving Studentsâ€™ Speaking Skill by Using Animation videoâ€. (An experimental study at the second year students of SMPN 1 Muara Tiga) - Farizawati Farizawati (Jurnal Sains Riset, 2017)
Speaking is an activity that has speaker, listener and also topic, problem and story. Animation Video is a film created by using a picture motion. Many of students interest with the video or film to disappear boring in studying. This study is aim to find that if the application of Animation Video will give better result on studentsâ€™ speaking skill. The population are all of students of SMP N I Muara Tiga that consist of 208 students. The writer took two classes as the sample. There were class IIa as an Experimental class and class IIb as a Control class which each of class consists of 18 students and total sample of the students were 36. To obtain the data, the writer gave pre-test and post-test as the instrument. The result showed that the significant different between the studentsâ€™ score in experimental class and control class. It could be seen from the result of mean of different for each of class in which the mean of difference score in experimental class was 26,38 while the mean of difference score in control class was 11,38. It showed the mean of difference score in experimental class was higher than the control class (26,38 > 11,38). It also could be seen from the result of the t-test score. The result of t-test score in the experimental class was 11,63 while the result of t-test score in control class was 3,44. It showed the t-test score on the experimental class was higher than control class (11,63 > 3,44). Meanwhile, the result of t-table with the level of significance with Df (É‘) 5% (0,05) was 2,03. It indicated that the t-test score (to) of both of the experimental class and control class was higher than t-table (tt). there are : (11,63 > 2,09) and (3,44 > 2,09). Because of to higher than tt, it concluded that Ha was accepted and Ho was rejected. Key words : Speaking, Animation Video